The Effects of Age and Initial Shoulder Posture on the Upper Limb Range of Harvesting Movements among Oil Palm Harvesters - Nelson Pady Tumit; Azmin Sham Rambely; Baba Md Deros (Applied Sciences, 2021)
The occurrence of musculoskeletal diseases (MSDs) among oil palm harvesters has been studied extensively, but there is a lack of published studies on the evaluation of the range of harvesting movements. This information is important to design the ergonomic tools needed in the manual harvesting of oil palm. We examined the upper limb motion of oil palm harvesters to determine the effects of age and initial shoulder postures on their range of harvesting movements. Twenty male harvesters performed a manual push-pull-cutting technique (≥3 m fresh fruit branches (FFBs) height). The study was conducted by capturing the 1-D push-pull cutting technique harvesting movement via the Quintic system at the sagittal plane. The active range of harvesting movements during the harvesting phases and the range of the harvesting movement of the initial and maximum postures of their upper arms were calculated based on the kinematic data generated with the Quintic Biomechanics system (Version 29). Participants were divided into three groups based on their age, and two groups based on their initial support shoulder position, and dominant shoulder position. Data were analysed using the ANOVA and t-test. The joint movement angle pattern of the harvesters was classified into three phases: preparation, execution, and ending. The age-related variances for the initial and maximum support shoulder postures were determined. The range of harvesting movements and the active range of harvesting movements during the preparation phase at the support shoulder and wrist region were also observed. The initial support shoulder posture displayed a statistical variance in the maximum support and dominant range of harvesting movements of the shoulder. It was also linked to a reduced active range of harvesting movements for the support shoulder flexion and dominant wrist ulnar deviation at the preparation phase. Furthermore, the initial dominant shoulder exhibited a statistically significant difference for the dominant arm and a reduced active range of harvesting movements in the dominant wrist ulnar deviation at the preparation phase. This study produced important evidence about factors to be considered for the ergonomic design of harvesting tools and workplaces, especially within the oil palm industry.